Study of clinical profile and outcome of viral hepatitis in children with reference to liver function test during covid pandemic admitted at tertiary care hospital - Patel, Pathik U.; Shah, Chirag D.; B., Abhishek M. (International Journal of Contemporary Pediatrics, 2024)
Background: Viral hepatitis is major health problem in both developing and developed country affecting millions of children worldwide. Viral hepatitis defined as inflammation of liver due to hepatotropic and/or non-hepatotropic viruses. Extent of disease vary from acute to chronic which ranges from asymptomatic to fatal acute and on other side from subclinical persistent to rapid progressive chronic disease. Aim of study was proportion and etiology with clinical profile and outcome relation to liver function test (LFT). Methods: This is retrospective observation study done at civil hospital, Ahmedabad during June 2019 to May 2021 during covid era in admitted patients from age of 6 month to 12 year diagnosed as viral hepatitis. Data collected from medical records and investigation from laboratory data. Results: In my study, Viral hepatitis was m/c seen in age group of 5 to 10 year in lower socioeconomic class with most common hepatotropic virus was hepatitis A (51.79%) and non-hepatotropic virus was dengue virus (17.86%). Most common presenting complain was fever (93.75%) and sign was jaundice (87.5%). Altered liver function seen in 96.57% patients. Outcome with 4.46% death due to covid19 virus. Conclusions: In my study during covid19 pandemic, still most common cause for viral hepatitis was hepatotropic virus–HEPATITIS A in admitted patients at tertiary care hospital. But case fatality rate was noted highest in COVID-19 virus among total death.